A review of government-led health and productivity management and disclosure practice in Japan - Yao, Jun; Johanson, Ulf (Frontiers in Sustainability, 2022)
The concept of occupational health and safety (OHS) is changing to include more job-related factors, resulting in an enlarged role for OHS management and a greater need for information disclosure in response to social expectations. It is vital for businesses to keep up with the new concept in health management and build a cohesive system if they are to achieve their sustainability goals. This paper examines current regulations and government initiatives to encourage health management and information sharing, as well as company practices in Japan, demonstrating that an increasing number of Japanese companies are adopting the new health management approach. We suggest a government-led H&PM model based on the Johanson and Aboagye (2020) model and best practices in Japan, demonstrating that legislation, policies, and implicit employee-centered stakeholder culture are important factors in the success of government-led projects. It also suggests that, to prevent window dressing and one-time booms, intrinsic motivation and psychological aspects should be researched and addressed more thoroughly.